Rice Yield Forecasting: A Comparative Analysis of Multiple Machine Learning Algorithms - Eli Adama Jiya; Umar Illiyasu; Mudashiru Akinyemi (Journal of Information System and Informatics, 2023)
Agriculture plays a crucial role in Nigeria's economy, serving as a vital source of sustenance and livelihood for numerous Nigerians. With the escalating impact of climate change on crop yields, it becomes imperative to develop models that can effectively study and predict rice output under varying climatic conditions. This study collected rice yield data from Katsina state, spanning the years 1970 to 2017, sourced from the Nigeria Bureau of Statistics. Additionally, climatic data for the same period were obtained from the World Bank Climate Knowledge portal. Logistic Regression (LR), Artificial Neural Network (ANN), Random Forest (RF), Random Trees (RT), and Naïve Bayes (NB) were employed to develop rice yield prediction models utilizing this dataset. The findings reveal that random forest and random trees exhibited superior classification performance for yield prediction. The developed models offer a promising tool for predicting future rice yields, facilitating proactive measures to ensure food security for the people of the state.